Pemanfaatan Sistem Informasi Geografis untuk Analisa Pola Distribusi Apotek di Kota dan Kabupaten Malang - Eva Monica; Kestrilia Rega Prilianti; Indah Lestari; Endhirayanti Caesarika (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
Health service facilities, especially pharmacies, play an important role in meeting the community's need for health support. A large number of pharmacies in Malang City and Regency is currently considered to be able to cause high competition between pharmacies so the geographic information system was chosen to see how the distribution of pharmacies is reviewed based on the population in each sub-district and the number of health facilities scattered in Malang. The purpose of this study was to determine the distribution pattern of pharmacies and their ratio to the total population density and health facilities in Malang City and Regency. The method used in this research is to collect data in the form of coordinate points of pharmacies and health facilities, followed by processing data in the form of a T index and using Arcgis 10.3 software to visualize it in the form of a map. In the analysis of the distribution of pharmacies in Malang City, the five sub-districts showed uniform or evenly distributed results, while in Malang District, out of 33 sub-districts, only 17 districts had a uniform pattern. Based on the ratio of pharmacies and the population of Kedungkandang District, it can be said to have the best accessibility, namely 1:1.010 (14:100,000), which has met the requirements set by the Ministry of Health and WHO. While the other 4 sub-districts in Malang City have met the requirements for pharmacists according to the Ministry of Health but have not met the requirements for pharmacists according to WHO. In Malang Regency, the standard of pharmacy service in terms of the ratio of the availability of pharmacies to the population has not been met, only 4 sub-districts have ratios that meet the requirements of the Ministry of Health but have not met the needs of WHO. The results of the ratio of pharmacies that were reviewed based on the number of health facilities showed that out of five sub-districts in Malang City, four other sub-districts namely Kedungkandang, Blimbing, Lowokwaru, and Klojen had a ratio with a good category, while Sukun District had a very good ratio. In Malang Regency, 17 sub-districts have a very good ratio, 3 sub-districts show a good ratio value, and 12 sub-districts have a ratio value of 0-0.9, indicating that the number of pharmacies in the sub-district is less than the number of health facilities.